2019
DOI: 10.1101/794248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imaging FCS Delineates Subtle Heterogeneity in Plasma Membranes of Resting Mast Cells

Abstract: A myriad of transient, nanoscopic lipid-and protein-based interactions confer a steady-state organization of plasma membrane in resting cells that is poised to orchestrate assembly of key signaling components upon reception of an extracellular stimulus. Although difficult to observe directly in live cells, these subtle interactions can be discerned by their impact on the diffusion of membrane constituents. Herein, we quantified the diffusion properties of a panel of structurally distinct lipid-anchored and tra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 103 publications
(149 reference statements)
2
14
0
Order By: Relevance
“…In contrast to EFR3B-GFP, the transmembrane protein TMEM150A-GFP showed a much slower recovery (t1/2 = 55±13 s), with a smaller mobile fraction (~60%) (Figs. 2B-C), consistent with studies indicating that the diffusion of transmembrane proteins is generally slower than lipidanchored proteins [34,35] . As a control experiment, we found that the FRAP recovery properties of TMEM150A-GFP were similar to its homolog TMEM150B-GFP, which is structurally very similar but not involved in formation of the PI4KIIIα complex [20] (Fig.…”
Section: Interactions Between Efr3b and Tmem150a Modulate Their Respective Membrane Dynamicssupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast to EFR3B-GFP, the transmembrane protein TMEM150A-GFP showed a much slower recovery (t1/2 = 55±13 s), with a smaller mobile fraction (~60%) (Figs. 2B-C), consistent with studies indicating that the diffusion of transmembrane proteins is generally slower than lipidanchored proteins [34,35] . As a control experiment, we found that the FRAP recovery properties of TMEM150A-GFP were similar to its homolog TMEM150B-GFP, which is structurally very similar but not involved in formation of the PI4KIIIα complex [20] (Fig.…”
Section: Interactions Between Efr3b and Tmem150a Modulate Their Respective Membrane Dynamicssupporting
confidence: 87%
“…The instrumental set-up, data acquisition and processing are described elsewhere [35] . Briefly, we collected time-lapse images (80,000 images at 3.5 ms frame rate) of ventral plasma membrane of fluorescently labelled RBL-2H3 cells using a home-built total internal reflection microscopy (TIRFM) equipped with high NA (1.49) oil-immersion objective and EMCCD camera (Andor iXon 897).…”
Section: Imaging Fluorescence Correlation Spectroscopy (Imfcs)mentioning
confidence: 99%
“…Phosphatidylcholines (PC) are present in both leaflets, and cholesterol flips rapidly between leaflets 5 . The outer leaflet lipids generally have more saturated chains than the inner leaflet yielding higher chain order and effective viscosity in the former, as shown by measurements of membrane order and diffusion 4,6,7 . The inner leaflet phospholipids have a net negative charge while the outer leaflet phospholipids are zwitterionic.…”
Section: The Plasma Membrane Maintains Lipid Asymmetry Across Outer and Inner Leafletsmentioning
confidence: 99%
“…Work in our and other laboratories has shown that diffusion of membrane components can be measured to monitor interactions within each leaflet as well as coupling between the leaflets. This has been particularly explored in the context of phase-dependent behaviors 4,7,44,53 . Microscopic phase separation in synthetic giant unilamellar vesicles and GPMVs is readily observed by diffraction-limited fluorescence imaging 28,54 .…”
Section: Diffusion Of Phase-selective Lipid Probes Reflects Underlying Phase-like Properties Of Plasma Membrane Leafletsmentioning
confidence: 99%
“…To illustrate, we draw on our own investigations of the transmembrane immunoreceptor (FceRI) in the PM of mast cells, which binds antigen-specific immunoglobulin E (IgE) (6). In its homeostatic steady state, the PM is a heterogeneous distribution of lipids (and accompanying proteins) into nanoscale domains that resemble the liquid-ordered (L o ) and liquid-disordered (L d ) phases defined in model membranes (7). The term "raft" is associated with the ordered, L o -like domains.…”
mentioning
confidence: 99%